(untitled) (Journal of Hama University, 2022)
This study aims at recognizing the relationship between the types of (thinking centre) according to Enneagram and the feeling of pleasure for Hearing Impaired Pupils in Assembly of Deaf and Blind in Hama City. The sample consisted of 50 male/female hearing impaired pupils, fifth and sixth grades, aged between 1(3-17) years. The study used the descriptive analytic approach by applying the standard of the types of thinking centre in Enneagram, prepared by Riso and Hudson, and oxford standard for pleasure. Data have been analyzed by SPSS. The study confirms the following results: -There is a strong positive relationship between the two types of thinking centre (the investigator and the enthusiast) and the feeling of pleasure. - There is no relationship between the personality type (loyalist) and feeling of pleasure. - There are statistically significant differences between the average means of the sample individuals on the scale of personality types (thinking centre) and the standard of feeling of pleasure according to gender variable for favour of females.